La gestión financiera y su repercusión en la rentabilidad económica de la Cooperativa de taxis “Alianza” año 2012 - Paredes Malta, Daniela Angélica (2013)
This research was conducted in order to know the effect of financial management on profitability and the reality of the financial situation in which the Cooperative is Taxis "ALLIANCE", besides knowing the opinion and judgment of those who administer and integrate. For the development of the research methods used inductive, deductive and analytic - synthetic which allowed me to study establishing facts through observation, analysis and classification of the information obtained to reach the conclusion of the problem, for it was applied a survey of members and interview the manager of the Cooperative valuable information that contributed greatly performing this work. The vertical analysis application to the financial statements of the fiscal year 2012, allowed to know the strengths and weaknesses of financial management takes place, so relevant financial indices applied in order to meet the financial and economic profitability Cooperative and as a result reflects an unfavorable situation, so it is necessary that after each accounting period to analyze the financial situation there is so efficient decision-making in terms of investment and financing adequate contributions to the growth, development and economic progress Cooperative financial.